Pengaruh Risiko Environmental, Social, and Governance (ESG) terhadap Enterprise Risk Management (ERM) dengan Kepemilikan Keluarga sebagai Variabel Moderasi - Mahclania, Arini; Helmy, Herlina (Universitas Negeri Padang, 2025)
The growing environmental issues that threaten Indonesia's economy present new challenges in maintaining corporate stability. The dynamics of these risks affect corporate performance, with Enterprise Risk Management (ERM) being one of the indicators affected. This study aims to evaluate the impact of Environmental, Social, and Governance (ESG) risks on ERM, with family ownership as a moderating variable in companies listed on the Indonesia Stock Exchange in 2024. This is a quantitative study. The study population includes companies listed on the Indonesia Stock Exchange. Using purposive sampling and secondary data sourced from IDX and Morningstar Sustainalytics, accessed via www.idx.co.id. The required data includes ESG risk scores and ERM-related disclosures. Hypothesis testing was conducted using moderation regression analysis with IBM SPSS 26t. The results indicate that ESG risk does not have a significant direct effect on ERM. However, family ownership significantly moderates the relationship between ESG risk and ERM.